Association of Low body Mass Index with Respiratory Failure in Chronic Obstructive Pulmunary Disease - Oli, Ritamvara; Mishra, Jai Krishna; Srivastava, Govind Narayan; Mishra, Saurabh (Journal of Nepal Health Research Council, 2021)
Background: Various studies have shown that low body mass index co-relates with the severity of Chronic obstructive pulmonary disease. The reduced body mass index in these patients is thought to be due to nutritional abnormality and raised circulating inflammatory markers. The study is aimed to find the association of body mass index with respiratory failure in patient with chronic obstructive pulmunory disease. Methods: 142 patients who attended emergency /out-patient-department in Sir Sundarlal Hospital from August 2018 to July 2020 were enrolled for the study. 81 patients in one group had chronic obstructive pulmonary disease exacerbation with Type II respiratory failure. Among this group low and normal body mass index subgroup was categorized.61 patients in another group had chronic obstructive pulmonary disease. Non-invasive ventilation was applied to case group. Categorization of body mass index was done <18.5(Low BMI) and 18.5-24.9 (Normal BMI ). Results: The mean age of the study group was (63.53±9.021). There was a significant difference in the body mass index between the groups ( p=<0.001,t=15.40). Severity of respiratory failure was compared using ph and pco2 in the between the groups which showed no significant difference (p=1,chi square 0.000), (p=0.40,chi square=0.72) however it did affect the outcome. Conclusions: Our study shows that overall respiratory failure was common in low body mass index cases compared to Control. Nevertheless there was no difference among severity of respiratory failure among low and normal body mass index subgroups and however it did affect the outcome. Keywords: Brain natriuretic peptide; chronic obstructive pulmonary diseases; non-invasive ventilation